How effective is media self-regulation? Results from a comparative survey of European journalists. (June 2015) - Fengler, Susanne; Eberwein, Tobias; Alsius, Salvador; Baisnée, Olivier; Bichler, Klaus; Dobek-Ostrowska, Boguslawa; Evers, Huub; Glowacki, Michal; Groenhart, Harmen; Harro-Loit, Halliki; Heikkilä, Heikki; Jempson, Mike; et al.
This article presents key results of a comparative journalists' survey on media accountability, for which 1762 journalists in 14 countries had been interrogated online. The article explores how European journalists perceive the impact of old versus new media accountability instruments on professional journalistic standards – established instruments like press councils, ethics codes, ombudsmen and media criticism, but also more recent online instruments like newsroom blogs and criticism via social media. Thus, the study also adds empirical data to the current debate about the future of media self-regulation in Europe, ignited by the Leveson Inquiry in the United Kingdom as well as the European Commission's High-Level Group on Media Freedom and Pluralism.